Effect of Conditioning Time on Standardized Ileal Digestibility of Amino Acids and Total Tract Digestibility of Energy in Diets Fed to Growing Pigs - Diego A. Lopez; Mason J. Engnell; Allison K. Blomme; Nelsa M. Beckman; Victoria C. Wilson; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2024)
Two experiments were conducted to determine the effect of conditioning time prior to pelleting on digestibility of energy and AA in swine diets. Treatments consisted of a mash diet, and three separate pelleted diets that were conditioned for either 30, 60, or 180 s prior to pelleting. For exp. 1, a total of 12 barrows (DNA 200 × 400, DNA; initially 99.1 ± 5.95 lb) were allotted to a replicated 4 × 4 Latin square design with four treatments and four periods for a total of 12 replicate pigs per treatment. Pigs were housed individually in metabolic crates equipped with a cup-drinker, a feeder, and partial metal diamond-slatted flooring. For each experimental period, the first 5 d were considered adaptation to the diet and during d 6-7 ileal digesta was collected. For exp. 2, a total of 12 barrows (DNA 200 × 400, DNA; initially 75.2 ± 2.27 lb.) were allotted to a replicated 4 × 3 balanced incomplete Latin square design with four treatments and three periods for a total of nine replicate pigs per treatment. Pigs were housed individually in the same metabolic crates as exp. 1. For each experimental period, the first 5 d were considered adaptation to the diet, and the following 5 d were considered the collection period. During collection, a screen and urine pan were installed to allow for the total and separate collection of feces and urine samples. For exp. 1, a treatment effect (P < 0.001) was observed for SID of CP, all indispensable AA, all dispensable AA, and total AA, excluding Lys, Met and Trp, which show no differences. The SID of CP, Arg, Leu, Thr, Ala, Ser, and Tyr was greater (P < 0.05) in the pelleted diets compared to the mash diet. For His, Ile, Phe, Val, Asp, and Glu, mash diets had decreased (P < 0.05) SID compared to the pelleted diets conditioned for 60 s and 180 s. However, there was no evidence of difference in SID of Val for any of the conditioning lengths. For SID of Cys, mash diets had decreased (P < 0.05) SID compared to the pelleted diets conditioned for 180 s, and there was no evidence of difference between the mash diets and pelleted diets conditioned for 30 s or 60 s. For the concentrations of DE and ME in both as-is and dry matter-basis, diets conditioned for 60 s had the greatest (P < 0.05) concentrations compared to the mash, 30 s, and 180 s treatments. These results indicated that long-term conditioning, up to 180 s, did not negatively impact AA acid digestibility or ME, and improved AA digestibility for certain AA compared to diets conditioned for 30 s. It was also demonstrated that conditioning the diets for 60 s optimized the DE and ME of the diet.
Keywords: amino acids; conditioning; digestibility; energy; growing pigs; pelleting